MODELING AUTOMATED BLOOD COLLECTION SYSTEMS WITH BIOMETRIC IDENTIFICATION - Яковенко, Ирина; Гребень, Илья (SWorldJournal, 2020)
This article substantiates the development of automated medical systems using biometric methods for identity identification. A structural and functional scheme was developed and 3D modeling of an automated biometric system of skin perforation with blood s